Fabrication of Iron Oxide/Zinc Oxide Nanocomposite Using Creeper Blepharis maderaspatensis Extract and Their Antimicrobial Activity - Abbas, Heba Salah; Krishnan, Akilandeswari; Kotakonda, Muddukrishnaiah (Frontiers in Bioengineering and Biotechnology, 2020)
Green nanotechnology has recently had a significant influence on advances in biological applications. The surface manipulation of iron oxide NPs by zinc-oxide is increasing attention for biomedical research. Therefore, this work focused on the phytochemicals of creeper Blepharis maderaspantensis (BM) water extract for synthesizing iron oxide NPs and iron oxide /zinc oxide nanocomposite. The UV spectrum analysis showed wavelength redshift from 294 nm to 302 nm of iron oxide/ZnO nanocomposite, and the polydispersity index revealed the perfect preparations of iron oxide NPs were prepared by boiling 0.25g of the plant in deionized water then the filtrate added to ferric chloride (1:1 v/v). The HRTEM results also illustrated that amorphous iron oxide NPs are spherical and irregular in shape. However, the iron oxide/ZnO nanocomposite showed rod-shaped of ZnO with an average length and width of ~19.25±3.2x3.3±0.6 nm surrounding amorphous iron oxide NPs. Furthermore, high antimicrobial activity with MRSA and E. coli was demonstrated by iron oxide NPs. However, because of instability and negative surface charge of the iron oxide nanocomposite, there was no antimicrobial activity. Future cytotoxic studies of the iron oxide NPs synthesized with polyphenols of BM extract are desirable, and their applications in medical purposes will be recommended.